Design of Electric Wheelchair Using Pulse Width Modulation (PWM) Method - Fidyatun Nisa; Dahlan Abdullah; Daniel Akhyar (Jurnal Informasi dan Teknologi, 2025)
An electric wheelchair is an essential mobility device for individuals with physical disabilities. Unlike traditional manual wheelchairs, which can be challenging for users to operate independently, an innovative PWM (Pulse Width Modulation) based electric wheelchair has been developed and tested. This wheelchair employs an Arduino Uno microcontroller, ultrasonic sensors, joystick input, and motor drivers to control speed and direction effectively. The system utilizes PWM to adjust the motor speed in proportion to the joystick input. Testing demonstrated that the wheelchair's motor responds efficiently to changes in PWM values. Additionally, the system successfully stops the motor when obstacles are detected within 80 centimeters. The ultrasonic sensors demonstrated an impressive measurement accuracy, with an average error of only 1%. Moreover, increasing the PWM values resulted in faster wheelchair speeds, showcasing the system’s ability for responsive speed control. This design provides an affordable and effective solution to improve mobility for users with disabilities.